Probing the multi-step crystallization dynamics of micelle templated nanoparticles: structural evolution of single crystalline γ-Fe2O3. Issue 18 (26th April 2019) - Liang, Kunyu; Hui, Lok Shu; Turak, Ayse
Abstract : Reverse micelle deposition of iron oxide nanoparticles results in monodisperse arrays of single crystalline nanoparticles with pure γ-Fe2 O3 or pure α-Fe2 O3 under optimized conditions, which can be effectively tracked from precursor incorporation through final particle formation using Raman spectroscopy. Abstract : Iron oxide nanoparticles synthesized with narrow size distribution were characterized using Raman spectroscopy, transmission electron microscopy and a superconducting quantum interference device magnetometer to investigate their composition, crystal structure and magnetic properties. Raman allowed us to explore the polymorphous transition of the iron oxide from the beginning of the synthesis process, as Raman can be used to monitor the precursors, the diblock-copolymer micelles and the resultant particles simultaneously under various processing steps. As different polymorphs possess distinct Raman active phonon modes, it also allows the identification of the exact phases of the resultant nanoparticles. Consequently, we show that the reverse micelle process results in pure phase nanoparticles only under certain conditions. Using insights obtained from examining the entire synthesis process, we can adjust the structure of small nanoparticles (∼6 nm) to achieve coercivity and saturation magnetization values that are usually only obtainable from larger particles (25 nm or larger). In this way, we show a route to tunable magnetic response based on the purity of the crystal phase rather than the particle size. By understanding the evolution of the entire synthesis process, it is possible to adjust the processing conditions to yield monodisperse single crystal phase nanoparticles for widespread use in a variety of applications.